THERAPEUTIC POSSIBILITIES OF THE CLASS II/1 ABNORMALITY IN EARLY TEMPORARY AND MIXED DENTITION - Viorica Ţărmure; Radu Septimiu Câmpian; Ecaterina Ionescu; Mariana Păcurar; Elina Teodorescu; Ştefan Milicescu; Paula Jiman; Mihaela Păstrăv; Andreea Pop (Amaltea Medical Publishing House, 2018)
Objectives. The establishment of the frequency of class II/1 in the requests of treatment in Clinica de Ortodontie Cluj between the years 2014 and 2017, the clinical and telegraphic evaluation of the cases with class II/1 and the therapeutically approach of class II/1 cases. Material and method. The study was made on a lot of 1,830 patients, which came to two of the clinics' offices. Results and discussions. The incidence of class II/1 at two of the Clinics offices between the years 2014 and 2017 was 47% (861 cases) of the total of studied cases. The repartition regarding the sexes showed a predominance of 69% at girls (592 cases). Conclusions. The frequency of class II/1 anomalies was high in treatment requests, 47%. Treatment in temporary and mixed dentition was done mainly with the functional appliances. The evolution of cases was favorable generally, demonstrated by clinical and cephalometric modifications.There were some limitations in the treatment with functional and removable appliances, the finishing stages will be done with fixed appliances.